Association between premature ovarian insufficiency, early menopause, socioeconomic status in a nationally representative sample from Korea. (March 2019) - Lim, Young-Mee; Jeong, Kyungah; Lee, Sa Ra; Chung, Hye Won; Lee, Wanhyung
Highlights: The possible association between POI or early menopause and socioeconomic status remains relatively unexplored. This study was performed using data from the Korea National Health and Nutrition Examination Survey. Our analysis revealed an increased risk of POI and early menopause among women of lower socioeconomic status. Abstract: Objective: We investigated whether, in the Korean population, the risk of premature ovarian insufficiency (POI) and early menopause varies with a woman's socioeconomic status, evaluated in relation to income, education, and occupation. Methods: This cross-sectional, population-based study involved 31, 508 women aged >19 years registered in the Korea National Health and Nutrition Examination Survey (KNHANES) (2007–2016). Menopausal status and socioeconomic status were obtained from self-reported KNHANES data. A logistic regression model was applied to test whether POI and early menopause varied with socioeconomic status. Results: The prevalence of POI was 2.41% and of early menopause was 5.89%. The annual incidence of POI during the investigation period plateaued, while that of early menopause showed a linear trend. The risk of POI was significantly higher among participants with lower household incomes (odds ratio [OR], 95% confidence interval [CI]; 1.44, 1.16–1.78) and lower levels of education (OR, 95% CI: 1.75, 1.16–2.65) after adjustment for age. Conclusion: The prevalence of POI in the Korean population was almost twice that reported in a previous study. Lower socioeconomic status was associated with an increased risk of POI and early menopause. Further studies are warranted to investigate this association.